2014
DOI: 10.1080/02687038.2014.955388
|View full text |Cite
|
Sign up to set email alerts
|

Profiling text comprehension impairments in aphasia

Abstract: Background: Research in aphasia has focused on acquired dyslexias at the single word level, with a paucity of assessment techniques and rehabilitation approaches for individuals with difficulty at the text level. A rich literature from research with paediatric populations and healthy non-brain damaged, skilled adult readers allows the component processes that are important for text reading to be defined and more appropriate assessments to be devised. Aims: To assess the component processes of text reading in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 60 publications
4
41
0
Order By: Relevance
“…There has now been more investigation of paragraph level reading, which is a closer approximation to everyday reading. Research has examined the nature of the reading difficulties, with characterisation of the influence of different types of information (Brookshire & Nicholas, 1993;Meteyard, Bruce, Edmundson, & Oakhill, 2015;Webster, Morris, Howard, & Garraffa, 2018) and the relationship between reading and other cognitive skills, for example, memory and executive function (Chesneau & Ska, 2015;Meteyard et al, 2015). Treatment studies at paragraph level have considered the impact of training oral reading or teaching various reading strategies on reading speed and reading comprehension (see Watter, Copley, & Finch, 2016 for a review of treatment for reading difficulties following acquired brain injury, including aphasia).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has now been more investigation of paragraph level reading, which is a closer approximation to everyday reading. Research has examined the nature of the reading difficulties, with characterisation of the influence of different types of information (Brookshire & Nicholas, 1993;Meteyard, Bruce, Edmundson, & Oakhill, 2015;Webster, Morris, Howard, & Garraffa, 2018) and the relationship between reading and other cognitive skills, for example, memory and executive function (Chesneau & Ska, 2015;Meteyard et al, 2015). Treatment studies at paragraph level have considered the impact of training oral reading or teaching various reading strategies on reading speed and reading comprehension (see Watter, Copley, & Finch, 2016 for a review of treatment for reading difficulties following acquired brain injury, including aphasia).…”
Section: Introductionmentioning
confidence: 99%
“…There is extensive variability in normal adults in the importance of reading, reading ability and preferences (Parr, 1992). Parr found that literacy activities (reading and writing) vary with a person's social network and roles, with delegation of some tasks to other people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cocks, Pritchard, Cornish, Johnson, & Cruice, 2013;Coelho, 2005;Meteyard, Bruce, Edmundson, & Oakhill, 2015). The reasons for reading difficulties can be myriad, as successful reading is based on the accurate and timely interplay of visual, linguistic and cognitive processes.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, pwABI experience discourse or text level reading comprehension deficits (i.e., occurring at a paragraph level or above) in the context of a cognitive-communication disorder (CCD) 14,15 , however these deficits may also occur following aphasia 16 . A recent systematic review investigated discourse level reading comprehension difficulties following ABI 17 .…”
Section: Introductionmentioning
confidence: 99%